A prospective evaluation of growth performance, health and welfare status in feedlot fattened dairy lambs under different feeding regimes - Tsimpouri, E; Lagonikou, M; Kalogianni, AI; Gelasakis, AI (Journal of the Hellenic Veterinary Medical Society, 2025)
The objective of this study was to prospectively assess the growth performance, health and welfare status in feedlot dairy breed lambs fattened under different feeding regimes. A total of 193, 3-month-old weaned lambs of two indigenous Greek breeds were enrolled in two longitudinal cohort studies. The first study (S1) included 75 Chios lambs and the second one (S2) 118 Serres lambs, which were randomly allocated into two groups. Each group was fed a diet containing either soybean meal (groups AC and AS, for Chios and Serres lambs, respectively) or canola meal (groups BC and BS, for Chios and Serres lambs, respectively) as its main protein source. Lambs were fattened for 13 weeks in S1 and 15 weeks in S2 to reach an average of ca. 35 to 40 kg pre-slaughter live body weight. Growth performance, and health and welfare indicators were recorded weekly during the fattening period. The most prevalent health and welfare problems in fattening lambs were nasal and ocular discharges. In group BC, body condition score and average daily gain were significantly increased [by 6.7% (P ≤ 0.001) and 12.9% (P < 0.05), respectively] compared to group AC. Moreover, group AC had significantly increased odds for nasal discharge compared to group BC [odds ratio (OR) = 1.59, P < 0.05], and group AS for ocular discharge (OR = 1.72, P < 0.05), and body abscesses (OR = 5.00, P ≤ 0.001) compared to group BS. Dairy lambs of Chios and Serres breeds demonstrated a satisfying fattening performance under different feeding regimes, despite the observed health and welfare challenges. The demand for further studies and interventions to improve feed efficiency and appropriately address health and welfare issues in feedlot fattening dairy lambs is evidenced.